Space-Confined Seeded Growth of Black Silver Nanostructures for Solar Steam Generation - Chen, Jinxing; Feng, Ji; Li, Zhiwei; Xu, Panpan; Wang, Xiaojing; Yin, Wenwen; Wang, Mozhen; Ge, Xuewu; Yin, Yadong (Nano letters, 2019)
Plasmonic metal nanostructures have attracted considerable attention for solar energy harvesting due to their capability in photothermal conversion. However, the narrow resonant band of the conventional plasmonic nanoparticles greatly limits their application as only a small fraction of the solar energy can be utilized. Herein, a unique confined seeded growth strategy is developed to synthesize black silver nanostructures with broadband absorption in the visible and near-infrared spectrum. Through this novel strategy, assemblages of silver nanoparticles with widely distributed interparticle distances are generated in rod-shaped tubular spaces, leading to strong random plasmonic coupling and accordingly broadband absorption for significantly improved utilization of solar energy. With excellent efficiency in converting solar energy to heat, the resulting black Ag nanostructures can be made into thin films floating at the air/water interface for efficient generation of clean water steam through localized interfacial heating.